Symposium policy note 4: Moving nutrition further up the development priority list in Egypt - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This policy note is one in a series of four notes that summarize key findings and recommendations from 32 seminars organized by IFPRI between 2016 and 2020 under the Evaluating Impact and Building Capacity Project funded by the United States Agency for International Development (USAID) and from related research done in collaboration with national and international partners in Egypt. The briefs have been prepared on the basis of a joint symposium and are intended to give policymakers and program designers in the areas of social protection, nutrition, agricultural policy, and the digitalization of agriculture a quick overview of research-based recommendations on key policy issues that will better enable Egypt to achieve several of the goals outlined in the Sustainable Development Strategy 2030. Addressing all forms of malnutrition – both undernutrition and overnutrition – remains a human and economic development challenge that Egypt must overcome. This brief highlights three areas of action to significantly improve the nutritional status of all Egyptians: Make domestic food policies more nutrition-sensitive and incentivize food producers and marketers to shift to the production, processing, and marketing of healthier foods. Expand ongoing awareness and educational campaigns, such as the 100 Million Healthy Lives initiative, to promote improved nutrition and to disseminate nutrition knowledge. The COVID-19 pandemic is an additional reminder and rationale for investing in healthy diets and sustainable food systems. Promote research to make nutrition policy more effective and efficient, including by increasing collection of nutrition-related data and better sharing of already collected data among ministries, research institutes, and other stakeholders.